Diabetes‐independent increase of factor VII‐activating protease activation in patients with Gram‐negative sepsis (melioidosis). (6th December 2014) - de Jong, H. K.; Koh, G. C. K. W.; Bulder, I.; Stephan, F.; Wiersinga, W. J.; Zeerleder, S. S.
Summary Background The plasma protease factor VII‐activating protease (FSAP) can release nucleosomes from late apoptotic cells. Nucleosomes are markers of cell death, and extracellular cell‐free DNA has been suggested to play an important role in inflammation and has been demonstrated to correlate with severity and outcome in sepsis patients. Objective To investigate FSAP activation in patients suffering from Burkholderia pseudomallei infection (melioidosis), an important cause of Gram‐negative sepsis in Southeast Asia. As diabetes mellitus (DM) is the most important risk factor for both melioidosis and sepsis, we were also able to examine the role of DM in FSAP activation in this cohort of patients. Methods In a prospective observational study, complexes of FSAP with α2‐antiplasmin (AP) were assayed in 44 patients with melioidosis, 34 of whom were classified as diabetic. Eighty‐two healthy subjects served as controls (52 with DM and 30 without). Results FSAP–AP complex levels were markedly elevated in patients as compared with controls. The FSAP level increased by 16.82 AU mL−1 in patients with melioidosis after adjustment for the effect of DM in the regression model. As expected, FSAP activation was correlated with nucleosome release (slope = 0.74). No difference in FSAP activation on admission was seen between survivors and non‐survivors, but the extent of FSAP activation correlated with stage of the disease; repeated testing during convalescence showed a return towards normal values (day 0 vs. day 28, 4.16 AU mL−1, 95% confidence interval [CI] 1.42–12.22). Conclusion Patients with Gram‐negative sepsis caused by B. pseudomallei have abundant FSAP activation, which significantly correlates with stage of disease. The presence of DM, however, does not influence the extent of FSAP activation.